Strategic Approaches to Monetization and Longevity in Indonesia’s Digital Startup Ecosystem: The Mediating Role of Business Model Agility - Sovania, Erina (Journal of Business, Finance, and Banking, 2025)
The failure of many digital startups in Indonesia, despite having promising ideas and early funding, has raised critical concerns about long-term sustainability and the ability to generate consistent revenue. This study investigates the strategic approaches to monetization and their influence on startup longevity, emphasizing the mediating role of business model agility. Using a quantitative approach, data were collected from 125 digital startups across Indonesia through structured questionnaires. The research employed Structural Equation Modeling (SEM) with SmartPLS to analyze the relationships among variables. The findings reveal that strategic monetization approach has a significant positive effect on both business model agility and startup longevity. Furthermore, business model agility also significantly influences startup longevity and mediates the relationship between monetization strategies and sustainability outcomes. These results underscore the importance of not only selecting the right monetization model but also maintaining flexibility and adaptability within the business model to achieve long-term viability. This study provides strategic insights for startup founders and ecosystem stakeholders to build more resilient and revenue-generating digital businesses.